THE EFFECT OF THE BOOK TAX GAP ON PROFIT PERSISTENCY IN FOOD COMPANIES AND DRINK LISTED ON BEI - Ade Khairuni Ritonga; Januri Januri (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this research is to test and obtain empirical evidence regarding the effect of the book tax gap on earnings persistence in Indonesia.This type of research isquantitative associative research. The population in this study is 26 manufacturing companies in the Food and Beverage Industry sector which are listed on the Indonesia Stock Exchange (IDX). The sample in this study were 10 manufacturing companies in the Food and Beverage Industry sector. The multiple analysis technique in this study uses simple regression, hypothesis testing and the coefficient of determination with the help of the SPSS V application. 22. The results of this study indicate that the difference between accounting profit and fiscal income has an effect on earnings persistence. The value of Adjusted R Square which is 0.820 indicates that the difference between accounting profit and fiscal profit on the earnings persistence variable is 82%.